The Lexical Status of the Root in Processing Morphologically Complex Words in Arabic. (3rd July 2016) - Shalhoub-Awwad, Yasmin; Leikin, Mark
ABSTRACT: This study investigated the effects of the Arabic root in the visual word recognition process among young readers in order to explore its role in reading acquisition and its development within the structure of the Arabic mental lexicon. We examined cross-modal priming of words that were derived from the same root of the target (/murattabun/-/tarti:bun/well ordered–order) relative to prime words that included three letters of the target but not root letters (/tura:bun/-/tarti:bun/soil-order) in two elementary-school age groups: second grade and fifth grade. The results showed facilitation in lexical decisions about target words, suggesting that the root is a lexical unit that plays a crucial role in the processing and representation of Arabic from the early stages of written language acquisition. This issue may stem from the morpho-orthographic nature of the written Arabic word and/or from the semantic information conveyed from the roots' morpheme.